2009
DOI: 10.3892/or_00000574
|View full text |Cite
|
Sign up to set email alerts
|

Glioma-astrocyte interaction modifies the astrocyte phenotype in a co-culture experimental model

Abstract: Abstract. As the majority of gliomas arise through malignant transformation of astrocytes, we aimed at investigating the interaction between malignant glioma cells and astrocytes in a co-culture experimental model. For this purpose we analyzed the expression of genes and proteins involved in tumor promotion and invasion, such as glial fibrillary acidic protein (GFAP), matrix metalloproteinase-2 (MMP-2), tissue inhibitor of MMP-2 (TIMP-2), transforming growth factor-ß1 (TGF-ß1), secreted protein acidic and rich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…Research has shown that the astrocyte phenotype can be transformed through GJC [27]. In the transwell co-culture experiments, GFAP and matrix metalloproteinase-2 (MMP-2) in astrocytes were upregulated, while tissue inhibitor of MMP-2 (TIMP-2) and secreted protein acidic and rich in cysteine (SPARC) were downregulated [44].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the astrocyte phenotype can be transformed through GJC [27]. In the transwell co-culture experiments, GFAP and matrix metalloproteinase-2 (MMP-2) in astrocytes were upregulated, while tissue inhibitor of MMP-2 (TIMP-2) and secreted protein acidic and rich in cysteine (SPARC) were downregulated [44].…”
Section: Discussionmentioning
confidence: 99%
“…Gagliano et al 42 have also shown that the co-culture of astrocytes with GBM cells increases the expression of MMP-2 and a decrease in TIMP-2 (tissue inhibitor of metalloproteinase) in astrocytes. Our work shows that GBM cells are able to modulate p53 expression of astrocytes, confirming that GBM is able to modulate protein expression of surrounding astrocytes as a way to favor malignancy.…”
Section: Resultsmentioning
confidence: 95%
“…A transwell co-culture system was used to confirm the chondroinductive role of soluble factors secreted by chondrocytes [22,23]. BMSC-scaffold constructs and chondrocyte-scaffold constructs were co-cultured in a transwell system separated by a semipermeable membrane (pore size: 0.4 mm) (Fig.…”
Section: In Vitro Co-culture Of Chondrocyte-scaffold Constructs and Bmentioning
confidence: 99%